From SWIGS to SWIMMR. Issue 5 (1st October 2021) - Rogers, Neil; Hübert, Juliane; Richardson, Gemma; Thomson, Alan
Abstract : Neil Rogers, Juliane Hübert, Gemma Richardson and Alan Thomson report from an RAS meeting that considered how to understand the potential hazard to our technology and infrastructure on the ground from extreme solar activity Abstract: Neil Rogers, Juliane Hübert, Gemma Richardson and Alan Thomson report from an RAS meeting that considered how to understand the potential hazard to our technology and infrastructure on the ground from extreme solar activity